TOXICITY TESTING WITH MARINE SEDIMENT ELUTRIATES FROM LOS CHIMUS, TORTUGAS AND CASMA BAYS IN PERU USING THE MICROALGAE Isochrysis galbana AND Nannochloropsis oceanica - López, Haydeé (2021)
Toxicity tests were carried out on marine sediment elutriates from Los Chimus, Tortugas, and Casma bays in Peru,   using   the   marine   microalgae   Isochrysis galbana   and Nannochloropsis oceanica. The marine sediment samples were collected in the months of March and August 2016. These toxicity tests were performed following standardized protocols, using static tests at 96 h of exposure. Previously, the sensitivity of both strains of microalgae was determined using copper sulfate (CuSO4·5H2O) as a reference substance. The mean Inhibition Concentration (IC50) obtained in this test showed that I. galbana was more sensitive than N. oceanica. Marine sediment elutriates from the study areas showed different levels of toxicity, such as "non-toxicity" (IC50 = 90% - 100%), "moderate toxicity" (IC50 = 59% - 81%), and "high toxicity" (IC50 < 59%) when using the microalgae I. galbana; while, in the case of N. oceanica, only “non-toxicity” (IC50 = 90% - 100%) was found for the same sediment elutriate samples. These toxicity tests show that the I. galbana microalgae detects different levels of toxicity, which is why it could be used to environmentally evaluate marine sediment samples as a complement to chemical tests since the origin of toxicity is not discriminated.